Architecture - Civilization - Gender. Residential Building, the civilizing process of dwelling practices and changes in the family. Bibliography architecture and gender. - Weresch, Katharina (Lit, 2015)
The book describes in line with Norbert Elias' civilizing process how architecture was perceived as well as dwelling practices over an extended period of societal development. The genealogy of the civilizing process in dwelling practices in Germany begins with the Palace of Versailles and runs chronologically to present day residential construction in Germany. Part B provides a bibliography of architecture and gender.
Keywords: Bebauung; Architektur; Architekt; Soziologie; Baugeschichte; Sozialpsychologie; Familie; Sozialwandel; Wohnungsbau; Wohngebäude; Gebäudetyp; Wohnen; Bibliographie; Architektursoziologie; Gender